Root initiation in cuttings and in vitro raised shoots of Pinus roxburghii - Kasana, Arvind Arya, Sandeep Kumar, M.S. (Journal of Phytology, 2015)
Rooting of in vitro produced buds and shoots is often the limiting step during micropropagation. Therefore, a better understanding of the various stages before and during root formation is needed. Reviewing the work done so far on Pines the present investigation was carried out to study the factors that affect in vitro rooting. Different parameters that influence rooting viz. donor age, phytohormones, and substrate were investigated. Shoots taken from field, it was found that the juvenility of the explant and position on the mother plant greatly affects the in vitro responses. In vitro raised shoots and hypocotyl cuttings of Pinus roxburghii showed best response over the other explants on ½ x DCR medium. Among the various auxins used in present investigation, NAA at lower concentrations found best for root initiation. Agar at 0.6% concentrations resulted in more healthy roots. Further elongation was achieved on ½ x DCR medium supplemented with lower concentrations of NAA. Present investigation was an attempt to establish an operative micropropagation protocol by improving the rooting of ‘hard to root’ Pinus roxburghii. In vitro rooting studies on Pinus roxburghii will be vital for enhanced multiplication and genetic improvement of this economically important forest tree species.